2023
DOI: 10.1051/e3sconf/202337400031
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste Product for Overcoming Heat Stress in Broilers

Abstract: Broiler farms in tropical areas have to deal with heat stress. Dried rice, a waste recycle product cheaper than corn, contains resistant starch that is mostly excluded from calorie-emanating metabolism yet advantageous for digestion. This study analyzes its potential to function as heat stress suppressor. Employing completely randomized design of three treatments in five repetitions, variables observed were panting frequency, heart weight, and blood profiles (leukocyte, heterophile, lymphocyte, and H:L ratio).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Moreover, other benefit of dry rice is increasing the intestinal performance because the apathogenic bacteria will grow optimally in the intestines. Such apathogenic bacteria produce an enzyme to maintain stability of the absorbed functions in the chicken's intestines [26,37].…”
Section: Weight Of Bursa Fabriciusmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other benefit of dry rice is increasing the intestinal performance because the apathogenic bacteria will grow optimally in the intestines. Such apathogenic bacteria produce an enzyme to maintain stability of the absorbed functions in the chicken's intestines [26,37].…”
Section: Weight Of Bursa Fabriciusmentioning
confidence: 99%
“…Dry rice not only has high palatability, but it can also be used as a substitute for corn and rice bran [25]. The use of dry rice in a broiler may reduce the heat stress as result of the research by Tonda et al [26]. But there has been no research to test the use of dry rice to maintain stability of immune by measuring variables of water consumption, weight of carcass, PCV value, weight of bursa fabricius and broiler antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Price differences between product types show the influence of appearance on consumer preferences and market demand. While T2 may have a higher price due to its clean appearance, T3 provides an opportunity for a cost-effective feed formulation, given its lower price and comparable nutritional content [53][54][55]. This suggests that feed manufacturers should consider the visual appeal and economic efficiency of raw materials when formulating feed products.…”
Section: Dried Rice Price Significancementioning
confidence: 99%
“…In this experiment, the temperature was relatively stable at 26 ℃ and, therefore inconsequential. However, a different duration may occur when feed is administered under heat stress; as discussed by Tonda et al (2023a), chickens in an environmental temperature of > 30 ℃ showed a better performance index when fed with "aking rice. "…”
Section: Feeding Durationmentioning
confidence: 99%